2021
DOI: 10.1097/phm.0000000000001727
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Every-Other-Day Fasting in the Treatment of Spinal Cord Injury

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In addition, a significant improvement in regional fat-free mass and a decrease in regional fat mass were observed in this group (42). In another RCT, an 8-week intervention with intermittent fasting led to a significant decrease in fasting glucose and body weight but did not influence BMI (43). A 7-month nutritional education with personalized diet in otherwise healthy SCI individuals did not influence blood pressure, lipid profile or anthropometric measurements (44).…”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 77%
“…In addition, a significant improvement in regional fat-free mass and a decrease in regional fat mass were observed in this group (42). In another RCT, an 8-week intervention with intermittent fasting led to a significant decrease in fasting glucose and body weight but did not influence BMI (43). A 7-month nutritional education with personalized diet in otherwise healthy SCI individuals did not influence blood pressure, lipid profile or anthropometric measurements (44).…”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 77%
“…EODF can exert neuroprotective effects and facilitate functional recovery in SCI rats. To allow clinical translation of EODF, we previously conducted a safety study of EODF in patients with SCI (Zheng et al, 2021), and although most of the subjects completed this clinical study, it was found through a post-survey follow-up that this dietary intervention required patients to endure hunger on fasting days, and that many SCI patients and families were less willing to attempt it again. We have also contemplated whether the gut microbiota after EODF intervention could be used as a clinical alternative to EODF.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 746 articles were identified from the initial database search. After title and abstract screening, full text screening was conducted on 224 articles, and nine RCTs with 899 participants whose nationality were Chinese (excluding subjects in intervention groups irrelevant to the review) were included in the meta-analysis [12,[17][18][19][20][21][22][23][24].…”
Section: Study Selectionmentioning
confidence: 99%
“…The study characteristics of the nine RCTs included in the meta-analysis are summarized in Table 1. In general, three trials evaluated 16:8 TRE [12,21,23], one evaluated 14:10 TRE [19], two studies evaluated the 5:2 diet [20,22], one evaluated ADF [24], and two trials evaluated both 16:8 TRE and ADF [17,18]. Among them, three RCTs conducted interventions with multiple arms [17,18,23].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation